The Effectiveness of Guidance and Individual and Group Counselling Services on the Mental Health Knowledge among Undergraduate and Postgraduate Students - Kuncharin, Linatda (Asia Social Issues, 2025)
The effectiveness of guidance and individual and group counseling services on mental health knowledge is important for undergraduate and postgraduate students. This study applied the mixed-methods sequential explanatory design, which aims to 1) examine the relationship between the effectiveness of guidance, individual, and group counseling services on the mental health knowledge among undergraduate and postgraduate students, 2) to explore the perception between undergraduate and postgraduate students with the mental health knowledge, and 3) to determine the effectiveness of guidance and individual and group counselling services on the mental health knowledge practiced by undergraduate and postgraduate students. The explanatory mixed method was used with 333 (84.73%) undergraduate and 60 (15.27%) postgraduate students; the questionnaires and semi-structured interviews were applied to collect the data. Descriptive statistics such as means, standard deviation, t-test, and correlation were using the Statistical Packet for Social Science (SPSS), and thematic analysis was performed on the interview data. The results showed that mental health knowledge is found to be relevant to the helpfulness of guidance service (t (391) = 2.24, p = 0.00) while confirmed by correlation analysis (r = 0.38**, p<0.00). The mental health knowledge is found to be relevant to the helpfulness of individual and group counseling services (t (391) = 1.18, p = 0.00) while confirmed by correlation analysis (r=0.29**, p<0.00). Moreover, the findings from the interviews with four students, they confirmed that had practiced by applying the guidance and individual counseling services and the mental knowledge when they were challenged facing the mental health issues.